Determinan Kepatuhan Wajib Pajak Orang Pribadi dalam Pelaporan SPT Tahunan pada Wajib Pajak Orang Pribadi Usahawan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research was conducted to identify and analyze the variables that influence the tax compliance of individual entrepreneurs in reporting their tax obligations. The independent variables studied include tax understanding, tax sanctions, tax administration, spiritual intelligence, and intellectual intelligence. The dependent variable is taxpayer compliance. This study employs a convenient sampling technique to determine the sample. The respondents in this study are individual entrepreneur taxpayers registered in Depok City, totaling 100. This research uses a questionnaire as the research instrument, structured using a Likert scale, and then analyzed using SPSS 26. The questionnaire was distributed online to the respondents and selected according to criteria. The results of the study indicate that tax understanding, tax sanctions, tax administration, spiritual intelligence, and intellectual intelligence have an influence on taxpayer compliance in submitting Annual Tax Returns. It is hoped that the findings of this study can serve as a guideline for the implementation of national taxation related to state revenue from the taxation sector